Production systems of village chickens - Hamid, Ramlah; Shukor, M. N. (1987)
A survey was carried out to study the production systems of village chicken with respect to identification of physical characteristics of breed, management and housing systems in several selected villages in Negeri Sembilan and Selangor. A total of 39 farmers were selected in this survey. The results indicated that the flock size were very small (23.1±5.6 to 52.0±23.1 birds), mainly reared under free range system and mixed farming were practiced especially with ducks. Two types of housing system were practiced by the farmers namely dirt floor and raised floor systems. The house design that were extensively seen were one with lean to roof type with wooden wall and slatted floor. Feeders and waterers were not widely used. The chicken were also provided with feed supplements such as wheat and paddy. Performances in term of growth and laying characteristic were low and there is no typical breed physical characteristics.